2003
DOI: 10.1097/00042728-200310000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Recalcitrant Dissecting Cellulitis of the Scalp With Complete Scalp Excision and Split-Thickness Skin Graft

Abstract: BACKGROUND. Dissecting cellulitis of the scalp (DCS) is a therapeutically challenging, chronic, progressive, suppurative disease of the scalp that is of unknown etiology. In addition to causing considerable discomfort and cosmetic disfigurement, long-standing lesions may result in the development of squamous cell carcinoma. Several treatment modalities for DCS have been employed with variable results. OBJECTIVE. To report the successful treatment of an aggressive, refractory case of DCS with complete scalp exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In 1986, Williams and colleagues first reported successful treatment with complete scalp excision followed by split‐thickness skin grafting 13 . Two recent reports also described the benefit of complete excision of the scalp for dissecting cellulitis 14,15 . It appears that, as with hidradenitis suppurativa, complete excision of the diseased skin results in long‐term remission of dissecting cellulitis.…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, Williams and colleagues first reported successful treatment with complete scalp excision followed by split‐thickness skin grafting 13 . Two recent reports also described the benefit of complete excision of the scalp for dissecting cellulitis 14,15 . It appears that, as with hidradenitis suppurativa, complete excision of the diseased skin results in long‐term remission of dissecting cellulitis.…”
Section: Discussionmentioning
confidence: 99%
“…Radical excision of affected areas in PCAS should theoretically be helpful. In 1967 Moschella et al described excision of large areas of affected skin [3] and in 2003 Bellow et al reported successful complete scalp excision and split‐thickness skin grafting [4]. Various treatment approaches with drug therapies are also discussed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…reported successful complete scalp excision and split-thickness skin grafting [4]. Various treatment approaches with drug therapies are also discussed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Low dose corticosteroids [163] Colchicine [60,64] Dapsone [60,64] Excision and skin grafting [165,166] Lasers and radiotherapy [167,168,169] Acne keloidalis nuchae [82,228] First line Potent topical steroids [65,170] Oral antibiotics+topical steroids/intralesional triamcinolone [65,170] …”
Section: Third Linementioning
confidence: 99%